Fault‐tolerant finite‐time adaptive higher order sliding mode control with optimized parameters for attitude stabilization of spacecraft. (9th December 2021) - Amrr, Syed Muhammad; Sarkar, Rajasree; Banerjee, Arunava; Saidi, Abdelaziz Salah; Nabi, Mashuq un
Abstract: This article considers the problem of attitude regulation of rigid spacecraft under the effect of inertial ambiguity, exogenous disturbances, input saturation, and actuator uncertainties. In this regard, an adaptive second‐order sliding mode control (ASOSMC) is designed to provide robustness against the lumped disturbances (the combination of uncertainties and faults). The ASOSMC presents a two‐fold advantage over conventional SMC. The use of adaptive law eliminates the assumption of a priori knowledge on the upper bounds of the disturbances. Further, the SOSMC methodology alleviates the high‐frequency chattering in the input without compromising robustness. The theoretical analysis under the proposed strategy guarantees the convergence of sliding surface and system states to the origin in a finite‐time. Besides, this work also resolves the inbuilt problem of unwinding in the quaternion‐based attitude representation. Further, the nominal parameters of the proposed control law are optimized offline using an ant lion optimization method. The numerical simulation validates the effectiveness of the proposed controller by comparing its performance with the other existing controllers.